আন্দামান, আবু, আজমিৰ আদি - Mitradev Sarma (Dr. Haren Chandra Deka, 2006)
The book is a collection of travel essays written by Mitradev Sharma based on the account of his travels.
Andaman, Abu, Ajmir Aadi...A Travel Account
Keywords: Assamese; Travel Account; Assamese